Contrasting between expectations and perceptions of service quality in the public bus transport system in Bogotá (2017)
Seeking to contribute to the field of management, and particularly to decision makers on public mobility policies, this article measures the perception of users of Bogotá's Integrated Public Transport System (SITP) in what has to do with the service quality. Using the Servqual approach, the analysis of gaps between expectations and perceptions of the service was performed. The results indicate that the variables that most affect the perception are safety and frequency of the routes. © 2017. revistaESPACIOS.com.